2010
DOI: 10.1111/j.1464-410x.2010.09841.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic botulinum toxin type A administration: evaluation of the effects on sexual function

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? Intraprostatic injection of botulinum toxin type A was shown to be effective in decreasing symptoms of BPH in several recent studies. However, the possible impairment of sexual function caused by the neurotoxin had never been investigated. This study shows that intraprostatic administration of botulinum toxin type A neither causes deterioration of sexual function (libido, orgasm, erectile function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…[ 41 ] , we confi rmed in the present study that intraprostatic BTX-A injection in patients with BPH does not impair erectile, orgasmic or ejaculatory functions and does not change libido. This is of utmost importance because sexual dysfunctions commonly occur in parallel with BPH [ 42 ] and are often associated with α -blockers and 5-ARIs.…”
Section: Discussionsupporting
confidence: 77%
“…[ 41 ] , we confi rmed in the present study that intraprostatic BTX-A injection in patients with BPH does not impair erectile, orgasmic or ejaculatory functions and does not change libido. This is of utmost importance because sexual dysfunctions commonly occur in parallel with BPH [ 42 ] and are often associated with α -blockers and 5-ARIs.…”
Section: Discussionsupporting
confidence: 77%
“…Intraprostatic injection of BoNT-A in patients with BPH does not impair erectile, orgasmic or ejaculatory functions and does not change libido [84]. The male hormonal profile is not altered by BoNT-A injection.…”
Section: Bont-a Effects In Human Prostatementioning
confidence: 85%
“…However, the studies have shown no consistency in clinical response in terms of outcome parameters such as symptom scores (for example, the American Urological Association Symptom Index [AUASI] and the International Prostate Symptom Score [IPSS]), reduction in prostate volume, postvoid residual urine volume, peak urinary flow rate (Q max ) and PSA (Table 1). [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] One intriguing finding is the observation that, even without a relevant impact on prostate volume in selected patients, the application of BoNT-A resulted in an increase in peak urinary flow rate and amelioration of LUTS. 65 This observation highlights the various pathophysiological aspects underlying LUTS suggestive of BPH.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Interestingly, the intraprostatic injection of BoNT-A does not seem to impair erectile, orgasmic and ejaculatory function. 64,78 One study even reported a significant improvement in ejaculatory function with no change in erectile function after injection of BoNT-A. 81 Adequately powered, randomized, placebo-controlled and blinded clinical trials are required to address essential aspects of BoNT-A treatment, such as the preferred route of administration (transperineal, transrectal or transurethral), optimal sites of injection, dose-dependent efficacy, long-term outcomes and safety profiles, which have not yet been defined.…”
Section: Mechanism Of Actionmentioning
confidence: 99%